2011
DOI: 10.1105/tpc.111.087015
|View full text |Cite
|
Sign up to set email alerts
|

Combined Noninvasive Imaging and Modeling Approaches Reveal Metabolic Compartmentation in the Barley Endosperm  

Abstract: The starchy endosperm of cereals is a priori taken as a metabolically uniform tissue. By applying a noninvasive assay based on 13 C/ 1 H-magnetic resonance imaging (MRI) to barley (Hordeum vulgare) grains, we uncovered metabolic compartmentation in the endosperm. 13 C-Suc feeding during grain filling showed that the primary site of Ala synthesis was the central region of the endosperm, the part of the caryopsis experiencing the highest level of hypoxia. Region-specific metabolism in the endosperm was character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
52
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 65 publications
0
52
0
Order By: Relevance
“…in Supplemental Table S1). The validity of the seed model has already been demonstrated in previous application studies (Grafahrend-Belau et al, 2009b;Melkus et al, 2011;Rolletschek et al, 2011).…”
Section: Reconstruction Of a Multiorgan Fba Modelmentioning
confidence: 70%
See 1 more Smart Citation
“…in Supplemental Table S1). The validity of the seed model has already been demonstrated in previous application studies (Grafahrend-Belau et al, 2009b;Melkus et al, 2011;Rolletschek et al, 2011).…”
Section: Reconstruction Of a Multiorgan Fba Modelmentioning
confidence: 70%
“…In recent years, the FBA approach has been applied to several different plant species, such as maize (Zea mays;Dal'Molin et al, 2010;Saha et al, 2011), barley (Hordeum vulgare;Grafahrend-Belau et al, 2009b;Melkus et al, 2011;Rolletschek et al, 2011), rice (Oryza sativa; Lakshmanan et al, 2013), Arabidopsis (Arabidopsis thaliana; Poolman et al, 2009;de Oliveira Dal'Molin et al, 2010;Radrich et al, 2010;Williams et al, 2010;Mintz-Oron et al, 2012;Cheung et al, 2013), and rapeseed (Brassica napus; Schwender, 2011a, 2011b;Pilalis et al, 2011), as well as algae (Boyle and Morgan, 2009;Cogne et al, 2011;Dal'Molin et al, 2011) and photoautotrophic bacteria (Knoop et al, 2010;Montagud et al, 2010;Boyle and Morgan, 2011). These models have been used to study different aspects of metabolism, including the prediction of optimal metabolic yields and energy efficiencies Boyle and Morgan, 2011), changes in flux under different environmental and genetic backgrounds (Grafahrend-Belau et al, 2009b;Dal'Molin et al, 2010;Melkus et al, 2011), and nonintuitive metabolic pathways that merit subsequent experimental investigations (Poolman et al, 2009;Knoop et al, 2010;Rolletschek et al, 2011). Although FBA of plant metabolic models was shown to be capable of reproducing experimentally determined flux distributions (Williams et al, 2010;Hay and Schwender, 2011b) and generating new insights into metabolic behavior, capacities, and efficiencies (Sweetlove and Ratcliffe, 2011), challenges remain to advance the utility and predictive power of the models.…”
mentioning
confidence: 99%
“…Some correlations have been established between transcriptional activity and metabolite concentration in the NP and ETCs of barley grains (Thiel et al, 2009). Studies on the metabolic compartmentation within developing barley grains so far showed local variation in endospermal sucrose and alanine concentration Rolletschek et al, 2011), which might be correlated to uneven levels of hypoxia within the grain (Rolletschek et al, 2004). Although it has long been known that fructosyl oligosaccharides are enriched in the endosperm cavity of the wheat (Triticum aestivum) grain during late storage (20 to 27 DAP) (Ugalde and Jenner, 1990;Schnyder et al, 1993), their role in grain development remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In most species, the immature seed is green for a period during its development, so during this phase it is regarded as being photoheterotrophic. A further level of complexity arises as a result of spatial heterogeneity within the seed (Rolletschek et al, 2011;Borisjuk et al, 2013a), which generates a significant degree of metabolic heterogeneity. Thousands of genes are involved in seed development.…”
mentioning
confidence: 99%